T(n) = 6T(n/3) + n * (n-1)
T(1) = 4
If we have a recurrence relation like above, what should we do?
--> a*T(n/b) + f(n)
--> a*T(n/b) + O(n^d)
--> 6*T(n/3) + O((n^2) - n)
--> 6*T(n/3) + O(n^2)
It seems to like we should use O(n^d). If we go through that way, result is O(n^2).
But I cannot be sure of that. It's like something is missing. Can anyone help to tell is this way true, how to solve this step by step? Thanks in advance.
In my opinion you can continue to apply the theorem to the next step :
with
According to the 1rst generic form of the master theorem : wikipedia